Discussing the evidence : small group work in the history class - Robinson, Andrew Meredith Lewin (Rhodes University, Faculty of Education, Department of Education, 1988)
This is a small-scale research study on the discovery method of teaching history through the medium of small-group discussion. The study begins with a brief outline of the theoretical background to these topics, as well as of some of the extant research in the field. The class selected for the study is the standard seven class of a boys' high school. After the researcher has instructed the whole standard in an historical area which is unfamiliar to the pupils, twelve groups of three each are selected and withdrawn from the rest of the class, one group at a time. These thirty-six pupils become the "experimental" group; the rest of the pupils become the "control" group . The groups are selected according to different intellectual criteria and presented with stimulus material of one of three kinds, which is intended to aid them in their discourse. Each group is given the same set of three questions to discuss and, without further assistance by the researcher, the discussion takes place. This is recorded on audio-tape. After all the group discussions have been recorded, an assessment test is given to the whole standard, both experimental and control pupils. At the end of the school term a compulsory examination question is inserted in the history examination. The statistical data forthcoming from these assessments are correlated and the results analysed. Meanwhile, transcripts of all the group discussions have been made and these are analysed on a qualitative basis in terms of the groups' intellectual composition and according to the type of stimulus material used, and the results are recorded. The concept of "leaderless" groups is briefly discussed in the light of the dealings of the various groups in the study. The researcher finally feels justified in concluding that small groups are an ideal medium for the handling of evidence- based learning in history. He also has certain observations to make on the performance of groups of mixed (as opposed to homogeneous) ability as well as on the success of certain types of stimulus material towards initiating profitable discussion.
Keywords: History -- Study and teaching (Secondary); Group work in education